The Implementation Of Strategy-Based Instruction To Improve Students’ Writing Skills - Pratiwi, Dwiyani (Journal of English and Education (JEE), 2012)
Learning strategy becomes an essential factor in the success of language learning. It is the first step for language learners to enhance their own learning because the learning strategies are tools for active, self-directed involvement, and essential to develop communicative competence (Oxford, 1990). Therefore, students need to be introduced to the various types of learning strategies through integrated strategy-based instruction. This research is aimed at improving students’ writing skills, which is focused on the improvement of students’ English grammatical competence through Strategy-Based Instruction (SBI). In this classroom action research, the students were engaged in a weekly integrated writing strategy-based instruction or training. They employed some learning strategies to improve their writing skills, i,e. writing difficult or new words and grammatical patterns on some small pieces of cards or mobile phones, using electronic dictionary, discussing their feeling with the lecturer, and practicing peer review, with a guided editing checklist. The findings show that there was an increase in the students’ awareness to use strategies (i.e. using mechanical techniques, highlighting, making efforts to find out how a word works in context by checking it in the dictionary, discussing the indiscipline attitude to the lecturer, and practicing peer review with a guided editing checklist). The finding also shows that the students’ grammatical competence as one of competences needed in writing improved. Key words: Strategy-Based Instruction, writing skills